Adjuvant Embolization with N-butyl Cyanoacrylate in the Treatment of Cerebral Arteriovenous Malformations: Outcomes, Complications, and Predictors of Neurologic Deficits - Starke, Robert M. (2009)
BACKGROUND AND PURPOSE: To assess the frequency, severity, and predictors of neurologic deficits following adjuvant embolization for cerebral arteriovenous malformations (AVMs). METHODS: From 1997-2006, 202 of 275 AVM patients received embolization prior to microsurgery (n=176) or radiosurgery (n=26). Patients were examined before and after endovascular embolization, and at clinical follow-up (mean 43.4±34.6 months). Outcome was classified according to the modified Rankin Scale (mRS). New neurological deficits after embolization were defined as minimal (no change in overall mRS), moderate (mRS≤2), or significant (mRS>2). RESULTS: 202 patients were treated in 377 embolization procedures. There were a total of 29 new clinical deficits after embolization (8% of procedures; 14% of patients), of which 19 were moderate or significant. Post-embolization deficits resolved in a significant number of patients over time (p<0.0001). Five patients suffered persistent neurological deficits due to embolization (1.3% of procedures; 2.5% of patients). In multivariate analysis, the following variables significantly predicted new neurological deficit following embolization: complex AVM with treatment plan specifying more than one embolization procedure (OR=2.7; 95% CI, 1.4-8.6), diameter <3cm (OR=3.2; 95%, CI 1.2-9.1), diameter >6cm (OR=6.2; 95% CI, 1.0-57.0), deep venous drainage (OR=2.7; 95% CI, 1.1-6.9) or eloquent location (OR=2.4; 95% CI, 1.0-5.7). These variables were weighted and used to compute an AVM Embolization Prognostic Risk Score for each patient. A score of 0 predicted no new deficits, a score of 1 predicted a new deficit rate of 6%, a score of 2 predicted a new deficit rate of 15%, a score of 3 predicted a new deficit rate of 21%, and a score of 4 predicted a new deficit rate of 50% (p<0.0001). CONCLUSIONS: Small and large size, eloquent location, deep venous drainage, and complex vascular anatomy requiring multiple embolization procedures are risk factors for the development of immediate post-embolization neurological deficits. Nevertheless, a significant number of patients with treatment-related neurological deficits improve over time. The low incidence of permanent neurological deficits underscores the utility of this technique in carefully selected patients.